Assessment of Factors Influencing Market Leadership and Innovation of FinTech Companies in the Digital economy - Anguelov, Kiril; Stoyanova, Tsvetana (Dr. Viktor Koval, 2025)
Introduction. The fintech industry has focused on its potential, as it has rethought the possibilities and put the provision of financial services in a digitally developed world on a completely different level. The digital transformation of financial services, made possible by the rapid development of new technologies that ensure reliable transactions, has boosted the growth of FinTech companies. Aim and tasks. The study aims to comprehensively assess the determinants of the ability of FinTech companies to achieve market leadership, sustain innovation activity, and ensure regulatory compliance in the context of the financial sector’s digital transformation. Results. The expert survey developed a standardised codebook to evaluate 15 FinTech companies grouped into three clusters, resulting in a composite index and validating hypotheses about the factors determining growth. The regulatory environment (RE, 0.148), trust and security (TS, 0.139), and access to finance (AF, 0.117) form the core determinants, followed by technological infrastructure (TI, 0.111) and team quality (TQ, 0.108), and the remaining factors have lower relative weights (<0.09). The inter-firm differences are mainly explained by the performance on the regulatory-trust and financial-technology determinants, and the sensitivity analysis shows that a 1-point (0–5) increase in RE/TS/AF increases the index by approximately +0.030/+0.028/+0.023, which quantitatively confirms their leading roles. A comparative analysis of the cohorts showed that the leaders (C1–C7) demonstrated high results (≥4 points on 9–10 factors out of 10) and significant superiority in technology infrastructure (TI) and team quality (TQ). At the same time, the remaining groups of companies had more fragmented profiles with pronounced weaknesses. Conclusions. FinTech growth relies on a core of regulatory stability (RE), trust and security (TS), and access to finance (AF), complemented by technological infrastructure (TI) and team quality (TQ). Predictable regulation, access to capital, high-security standards, and targeted partnerships maximise the chance of “gazelle” or “unicorn” growth. A predictable regulatory environment and access to investment capital play a key role in accelerating the growth of the FinTech ecosystem. FinTech management should prioritise investments in technology infrastructure, developing highly skilled teams, creating targeted partnerships and ecosystems (PEs), and developing scalability and international expansion (SIEs) to transform high-growth companies into leaders.